Comparative Studies of Ontologies on Sarawak Gazette - Fatihah, Ramli; Bali, Ranaivo-Malançon; Stephanie Chua, Hui Li; Mira Shumiza, Mohammad (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
This paper presents a discussion on experience and process during initial stage of ontology building in history. The objective of this paper is to create a manual semantic annotation process to determine the concepts that will be used in the historical news ontology. It will describe the tasks of facilitating the analysis of missing concepts existing in Sarawak Gazette (SAGA) documents. Semantically annotating SAGA documents enable to enrich the element of concepts and relations taken from existing ontologies. Furthermore, an initial result is provided to observe the performance gain due to domain specific annotations. Finally, we conclude on the importance of semantic annotations process in the construction of an ontology.